If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(z + 4) + -2(z + -2) = 3(z + -2) + 4(z + -1) Reorder the terms: 10(4 + z) + -2(z + -2) = 3(z + -2) + 4(z + -1) (4 * 10 + z * 10) + -2(z + -2) = 3(z + -2) + 4(z + -1) (40 + 10z) + -2(z + -2) = 3(z + -2) + 4(z + -1) Reorder the terms: 40 + 10z + -2(-2 + z) = 3(z + -2) + 4(z + -1) 40 + 10z + (-2 * -2 + z * -2) = 3(z + -2) + 4(z + -1) 40 + 10z + (4 + -2z) = 3(z + -2) + 4(z + -1) Reorder the terms: 40 + 4 + 10z + -2z = 3(z + -2) + 4(z + -1) Combine like terms: 40 + 4 = 44 44 + 10z + -2z = 3(z + -2) + 4(z + -1) Combine like terms: 10z + -2z = 8z 44 + 8z = 3(z + -2) + 4(z + -1) Reorder the terms: 44 + 8z = 3(-2 + z) + 4(z + -1) 44 + 8z = (-2 * 3 + z * 3) + 4(z + -1) 44 + 8z = (-6 + 3z) + 4(z + -1) Reorder the terms: 44 + 8z = -6 + 3z + 4(-1 + z) 44 + 8z = -6 + 3z + (-1 * 4 + z * 4) 44 + 8z = -6 + 3z + (-4 + 4z) Reorder the terms: 44 + 8z = -6 + -4 + 3z + 4z Combine like terms: -6 + -4 = -10 44 + 8z = -10 + 3z + 4z Combine like terms: 3z + 4z = 7z 44 + 8z = -10 + 7z Solving 44 + 8z = -10 + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. 44 + 8z + -7z = -10 + 7z + -7z Combine like terms: 8z + -7z = 1z 44 + 1z = -10 + 7z + -7z Combine like terms: 7z + -7z = 0 44 + 1z = -10 + 0 44 + 1z = -10 Add '-44' to each side of the equation. 44 + -44 + 1z = -10 + -44 Combine like terms: 44 + -44 = 0 0 + 1z = -10 + -44 1z = -10 + -44 Combine like terms: -10 + -44 = -54 1z = -54 Divide each side by '1'. z = -54 Simplifying z = -54
| -32-9y=23 | | 27/21=X/28 | | x^2+128x-256=0 | | t=(.10+2.15)873.36 | | (8x^2-3x^3)-(2x^2-7x^3)= | | t=(0.010+2.15)873.36 | | -16-9y=-24 | | x^3+30x^2-400=0 | | 16-9y=-24 | | 2b=-0.6 | | 25e^x/5 | | x^-2/3=16 | | 13x+15y=1 | | 8+3h=25 | | 8sin^2(5x)=4 | | 6.5x+5.15x=200 | | (3x-7y)-(x+2y)= | | x^2+3=2 | | ln(x-5)+ln(x)=0 | | 3(2x+4)=2+6+10 | | 5(1-5)+15-6+24+20= | | (6x^2y^-3z^4/3x^5y^-3z^1)^2 | | 10=35x | | 6/11*4/7 | | 3(x-4)(x-4)= | | 5(2X-8)+6=4x-32 | | 4/3m= | | -16+5(-4)-9=x | | e^3x+2=40 | | -sx=-15 | | 18(5c-1)-2=88c+18 | | 22=A+4B-4C |